2012
DOI: 10.3892/mco.2012.44
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic breast cancer in patients with schizophrenia

Abstract: Abstract. Breast cancer is a major health problem worldwide. The median survival duration for patients with metastatic breast cancer is two to three years. Approximately 1% of populations worldwide have schizophrenia. The manner in which schizophrenic patients fare when diagnosed with metastatic breast carcinoma (MBC) was evaluated. We queried the National Department of Veterans Affairs (DVA) datasets using computer codes for a pre-existing diagnosis of schizophrenia and a later diagnosis of breast carcinoma. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…Furthermore, Meyer et al reported that it is difficult for those with psychiatric disorders, particularly schizophrenia, to accomplish chemotherapy within a protocol, because they often fail to understand the nature of their illnesses. 5 As a result, it is particularly challenging to treat patients with testicular cancer who have psychiatric disorders. However, little is known about the impact of severe psychiatric disorders on the clinical outcome of patients with testicular cancer.…”
mentioning
confidence: 99%
“…Furthermore, Meyer et al reported that it is difficult for those with psychiatric disorders, particularly schizophrenia, to accomplish chemotherapy within a protocol, because they often fail to understand the nature of their illnesses. 5 As a result, it is particularly challenging to treat patients with testicular cancer who have psychiatric disorders. However, little is known about the impact of severe psychiatric disorders on the clinical outcome of patients with testicular cancer.…”
mentioning
confidence: 99%
“…Os psiquiatras fornecem apoio psicológico, tranquilidade, educação, encaminhamentos para apoio à saúde mental da comunidade e conhecimento especializado sobre usos de medicamentos antipsicóticos (Block, 2006) (Meyer, et al, 2013).…”
Section: Resultsunclassified